Constructing Identities: Amos Tutuola and the Ibadan Literary Elite in the wake of Nigerian Independence - Mackenzie Finley (Yoruba Studies Review)
With Nigerian novelist Amos Tutuola as primary subject, this paper at[1]tempts to understand the construction of sociocultural identities in Nigeria in the wake of independence. Despite the international success of his literary publications, Tutuola was denied access to the most intimate discourses on the development of African literature by his Nigerian elite contemporaries, who emerged from University College, Ibadan, in the 1950s and early 1960s. Having completed only a few years of colonial schooling, Tutuola was differentiated from his elite literary contemporaries in terms of education. Yet if education represented a rather concrete, institutionalized divide between the elite and the everyday Nigerian, this paper will suggest that the resulting epistemological difference served as a more fluid, ideological divide. Both Western epistemology, rooted in Western academic spaces, and African epistemology, preserved from African traditions like proverbs and storytelling, informed the elite and Tutuola’s worldviews. The varying degrees to which one epistemology was privileged over the other reinforced the boundary between Tutuola and the elite. Furthermore, educational experiences and sociocultural identities informed the ways in which independent Nigeria was envisioned by both Tutuola and the elite writers. While the elites’ discourse on independence reflected their proximity to Nigeria’s political elite, Tutuola positioned himself as a distinctly Yoruba writer in the new Nigeria. He envisioned a state in which traditional knowledge remained central to the African identity. Ultimately, his life and work attest to the endurance of indigenous epistemology through years of European colonialism and into independence. 148 Mackenzie Finley During a lecture series at the University of Palermo, Italy, Nigerian novelist Amos Tutuola presented himself, his work, and his Yoruba heritage to an audience of Italian students and professors of English and Anglophone literatures. During his first lecture, the Yoruba elder asked his audience, “Why are we people afraid to go to the burial ground at night?” An audience member ventured a guess: “Perhaps we are afraid to know what we cannot know.” Tutuola replied, “But, you remember, we Africans believe that death is not the end of life. We know that when one dies, that is not the end of his life [. . .] So why are all people afraid to go to the burial ground at night? They’re afraid to meet the ghosts from the dead” (emphasis in original).1 Amos Tutuola (1920–1997) was recognized globally for his perpetuation of Yoruba folklore tradition via novels and short stories written in unconventional English. His works, especially The Palm-Wine Drinkard (1952) and My Life in the Bush of Ghosts (1954), were translated into numerous European languages, including Italian. Given the chance to speak directly with an Italian audience at Palermo, Tutuola elaborated on the elements of Yoruba culture that saturated his fiction. His lectures reflected the same sense of purpose that drove his writing. Tutuola explained, “As much as I could [in my novels], I tried my best to bring out for the people to see the secrets of my tribe—I mean, the Yoruba people—and of Nigerian people, and African people as a whole. I’m trying my best to bring out our traditional things for the people to know a little about us, about our beliefs, our character, and so on.”2 Tutuola’s didactics during the lecture at Palermo reflect his distinct intellectual and cultural commitment to a Yoruba cosmology, one that was not so much learned in his short years of schooling in the colonial education system as it was absorbed from his life of engagement with Yoruba oral tradition. With Tutuola as primary subject, this paper attempts to understand the construction of sociocultural identities in Nigeria in the wake of independence. The educated elite writers, such as Wole Soyinka and Chinua Achebe, who emerged from University College, Ibadan, during the same time period, will serve as a point of comparison. On October 1, 1960, when Nigeria gained independence from Britain, Tutuola occupied an unusual place relative to the university-educated elite, the semi-literate “average man,” the international 1 Alassandra di Maio, Tutuola at the University: The Italian Voice of a Yoruba Ancestor, with an Interview with the Author and an Afterword by Claudio Gorlier (Rome: Bulzoni, 2000), 38. The lecture’s transcriber utilized graphic devices (italicized and bolded words, brackets denoting pauses and movements) to preserve the dynamic oral experience of the lecture. However, so that the dialogue reads more easily in the context of this paper, I have removed the graphic devices but maintained what the transcriber presented as Tutuola’s emphasized words, simply italicizing what was originally in bold. 2 Di Maio, Tutuola at the University, 148. Constructing Identities 149 stage of literary criticism, and the emerging field of African literature. This position helped shape his sense of identity. Despite the success of his literary publications, Tutuola was not allowed to participate in the most intimate dis[1]courses on the development of African literature by his elite contemporaries. In addition to his lack of access to higher education, Tutuola was differentiated from his elite literary contemporaries on epistemological grounds. If education represented a rather concrete, institutionalized divide between the elite and the everyday Nigerian, an epistemological difference served as a more fluid, ideological divide. Both Western epistemology, rooted in Western academic spaces, and African epistemology, preserved from African traditions like proverbs and storytelling, informed the elite and Tutuola’s worldviews. The varying degrees to which one epistemology was privileged over the other reinforced the boundary between the elite and Tutuola. This paper draws largely on correspondence, conference reports, and the personal papers of Tutuola and his elite contemporaries housed at the Harry Ransom Center at the University of Texas at Austin, as well as on interviews transcribed by the Transcription Centre in London, the periodical Africa Report (1960–1970), and Robert M. Wren and Claudio Gorlier, concentrating on primary sources produced during the years immediately prior to and shortly after Nigerian independence in 1960. Tutuola’s ideas generally did not fit into the sociocultural objectives of his elite counterparts. Though they would come in contact with one another via the world of English-language literature, Tutuola usually remained absent from or relegated to the margins of elite discussions on African creative writing. Accordingly, the historical record has less to say about his intellectual ruminations than about those of his elite contemporaries. Nonetheless, his hand-written drafts, interviews, and correspondences with European agents offer a glimpse at the epistemology and sense of identity of an “average” Nigerian in the aftermath of colonialism and independence.